Dual-core–shell structure B@LiF@AP with multi-effect synergies to improve processibility and energy release characteristics of B. Issue 3 (3rd January 2023) - Wang, Deqi; Liu, Jie; Tan, Tianyu; Liu, Shishuo; Xu, Guozhen; Zhang, Zhimiao; Qin, Yang; Li, Fengsheng
Abstract : A dual-core–shell structure, B@LiF@AP, B embedded with LiF as core and AP as shell, with multi-effect synergies, has been designed and successfully prepared to improve processibility, ignition and combustion of B. Abstract : Boron (B) is the most suitable fuel for rocket ramjet. However, boron oxide (B2 O3 ) on the surface of B causes many problems in its application. B2 O3 cross-links with hydroxyl prepolymer, which reduces the processibility of the system. Moreover, B2 O3 hinders contact between the oxidation component and internal active B. Consequently, B is difficult to ignite, and its reactivity and combustion efficiency are limited. To solve these problems, a dual-core–shell structure, B@LiF@AP, B embedded with LiF as core and AP as shell, has been designed and prepared. Its multi-effect synergies, improving processibility, protecting B from oxidation by AP before burning, decomposing B2 O3, and improving reactivity and combustion efficiency, have been confirmed. Compared with the mixed sample of B and AP (B–AP), the heat release of B@LiF@AP increased by 211.10%. The combustion efficiency of B@LiF@AP increased by 42.60% more than that of B@AP. The ignition test showed that its ignition energy was reduced by 37.89% and the flame temperature increased by 26.27% than that of B–AP. The application and development of boron-based rocket ramjet will be accelerated because the application problems of B are solved by B@LiF@AP.